Method for separating woody biomass components by using medium-boiling-point alcohol ether compounds

By using medium-boiling-point alcohol ether compounds and adjusting the pH value, efficient separation of biomass components and solvent recovery are achieved, solving the problems of high temperature, high pressure and high energy consumption in the existing technology, and reducing production costs and waste liquid emissions.

CN120665315APending Publication Date: 2025-09-19SHANDONG BAIMUSHENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510785560.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-12
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing biomass organic solvent pretreatment methods have problems such as high temperature and high pressure requirements, high equipment costs, high energy consumption for solvent recovery, and serious product pollution, making it difficult to achieve efficient and low-cost separation of biomass components.

Method used

Medium-boiling-point alcohol ether compounds are used as solvents, and the reaction is carried out by adjusting the pH value to separate the cellulose, lignin and hemicellulose components. The solvent is recovered by drying and distillation, avoiding the use of large amounts of water.

Benefits of technology

The efficient separation of the three components of biomass can be achieved at a lower temperature, the degradation of lignin and hemicellulose can be inhibited, the industrial production cost can be reduced, the waste liquid discharge can be reduced, and the solvent recovery rate can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical engineering, and particularly relates to a method for separating a woody biomass component by using a medium-boiling-point alcohol ether compound. According to the method, the vicinal diol monoether compound containing hydroxyl and ether bonds is used for biomass pretreatment, efficient separation of three components of biomass is achieved at a low temperature, and meanwhile the beneficial effects of inhibiting degradation of lignin and hemicellulose sugar and the like are achieved. In addition, the residual solvent is recovered by drying solid residues and concentrating the pretreatment filtrate, so that the use of a large amount of water in the solvent recovery project is avoided, the industrial production cost is reduced, the waste liquid discharge in the pretreatment process is reduced, and the problem of the solvent recovery rate in the wood biomass pretreatment process is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical engineering, and particularly relates to a method for separating wood biomass components by utilizing medium-boiling point alcohol ether compounds. Background Art

[0002] With the global energy transition, the non-renewable nature and negative environmental externalities of traditional fossil fuels are becoming increasingly prominent. Against this backdrop, the development of clean, renewable energy alternatives has become a global consensus. As the most abundant renewable resource in terrestrial ecosystems, lignocellulosic biomass is considered one of the most promising alternatives to fossil fuels due to its carbon neutrality, renewability, and abundant reserves.

[0003] The key to efficient utilization of biomass resources lies in the effective separation and conversion of the three major components: cellulose, hemicellulose, and lignin. Pretreatment, as the primary step in biomass refining, directly impacts subsequent conversion efficiency and product value. Organic solvent fractionation is considered one of the most promising pretreatment technologies due to its excellent lignin removal rate and cellulose accessibility. Studies have shown that acidic organic solvent pretreatment significantly outperforms traditional dilute acid pretreatment in terms of lignin removal rate and causes less damage to the cellulose structure.

[0004] Currently, organic solvents used in biomass organic solvent pretreatment methods are primarily categorized into two main groups: low-boiling-point solvents (such as tetrahydrofuran, ethanol, dioxane, formic acid, and acetic acid) and high-boiling-point solvents (such as ethylene glycol, 2,3-butanediol, and γ-valerolactone). While low-boiling-point solvents offer the advantage of easy recovery, they also have significant drawbacks. For example, dioxane and tetrahydrofuran can achieve good lignin removal rates at temperatures as low as 80°C. However, these solvents are potentially toxic, requiring stringent process containment and wastewater treatment requirements. The resulting products contain residual dioxane, making them unsuitable for downstream food-grade production. Alcohols such as ethanol and butanol require high temperatures and pressures for pretreatment to achieve good lignin removal, but this increases equipment investment costs and can easily cause thermal degradation of cellulose and hemicellulose. Formic acid and acetic acid are odorous and highly corrosive, requiring high equipment containment and corrosion resistance. High-boiling-point solvents such as γ-valerolactone require extensive water washing during recovery, followed by energy-intensive water evaporation for solvent recovery.

[0005] Therefore, developing a medium-boiling-point, water-free or low-water-consumption method for separating woody biomass components is of great practical significance for reducing pretreatment costs and improving process economy. Summary of the Invention

[0006] Based on the above technical problems, the object of the present invention is to provide a method for separating wood biomass components using medium-boiling point alcohol ether compounds.

[0007] To achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for separating woody biomass components using medium-boiling point alcohol ether compounds, comprising the following steps: S1. Mixing plant wood, a vicinal glycol monoether compound, water, and an acid, reacting the mixture in a closed reactor for 0.5 to 5 hours, adjusting the pH to 6 to 7, and separating to obtain a cellulose solid component and a filtrate A; S2. Drying the cellulose solid component to a constant weight to obtain a cellulose component, condensing and recovering the solution containing the vicinal glycol monoether compound during the drying process, distilling the filtrate A to recover the solution containing the vicinal glycol monoether compound to obtain a residue, adding water to the residue, stirring, and performing solid-liquid separation to obtain a lignin solid component and a filtrate B; S3. Dry the lignin solid component to a constant weight to obtain a lignin component, and adjust the pH of the filtrate B to 0.6-0.8 and hydrolyze for 0.5-1.5 h to obtain a hemicellulose sugar component.

[0008] The method provided by the present invention utilizes medium-boiling-point alcohol-ether compounds with boiling points between 120°C and 140°C, which is higher than traditional low-boiling-point solvents but lower than traditional high-boiling-point solvents. These compounds combine the advantages of both alcohol and ether compounds, inhibiting lignin condensation reactions and sugar degradation. They also exhibit excellent lignin dissolution capabilities, improving lignin removal rates. Furthermore, the method provided by the present invention utilizes drying and distillation steps for solvent recovery, avoiding the use of large amounts of water in the solvent recovery process and reducing industrial production costs.

[0009] Furthermore, the vicinal glycol monoether compound is selected from any one of ethylene glycol monomethyl ether, 1,2-propylene glycol-1-monomethyl ether, ethylene glycol monoethyl ether, and 1,2-propylene glycol-1-monoethyl ether.

[0010] Furthermore, the mass ratio of the plant wood, vicinal glycol monoether compound, water and acid in S1 is 0.5~2.5:5~15:0.5~4.5:0.01~0.3.

[0011] Furthermore, the reaction conditions in the closed reactor are 80-140° C. and 90-110 kPa.

[0012] Furthermore, the drying conditions are 80-120° C. and 0.001-0.1 MPa.

[0013] Furthermore, the mass ratio of the residue to water in S2 is 0.5-1.5:9-11.

[0014] Furthermore, the distillation conditions are 80-120° C. and 0.001-0.1 MPa.

[0015] Furthermore, the acid is selected from any one of 98% by mass sulfuric acid, 37% by mass hydrochloric acid and 85% by mass phosphoric acid.

[0016] The present invention has the following beneficial effects: The present invention utilizes vicinal glycol monoether compounds containing hydroxyl groups and ether bonds for biomass pretreatment, achieving the beneficial effects of efficient separation of the three biomass components at relatively low temperatures while simultaneously inhibiting the degradation of lignin and hemicellulose sugars. Furthermore, residual solvent is recovered by drying the solid residue and concentrating the pretreatment filtrate, avoiding the use of large amounts of water in the solvent recovery process. This reduces industrial production costs, minimizes wastewater discharge during the pretreatment process, and addresses the issues of high energy consumption and low solvent recovery rates in woody biomass pretreatment. DETAILED DESCRIPTION

[0017] The present invention is described in detail below with reference to specific examples, but these examples should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the following examples are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.

[0018] Example 1 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid component and a filtrate. The cellulose-containing solid component was distilled at 80°C and 0.001 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose component. The filtrate was distilled at 80°C and 0.001 MPa to recover the solvent, and the recovered solvents were combined. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin component. The filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0019] Example 2 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 10.2 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 5 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 90°C and 0.005 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.005 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0020] Example 3 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of Masson pine were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% potassium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid component and a filtrate. The cellulose-containing solid component was distilled at 100°C and 0.01 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose component. The filtrate was distilled at 100°C and 0.01 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin component. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0021] Example 4 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of eucalyptus powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% potassium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid component and a filtrate. The cellulose solid component was distilled at 100°C and 0.01 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose component. The filtrate was distilled at 100°C and 0.01 MPa to recover the solvent, and the recovered solvent was combined and weighed. To the filtrate residue after solvent recovery, 10 times the mass of water was added, stirred, and then solid-liquid separation was performed. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin component. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0022] Example 5 9 g of propylene glycol monomethyl ether, 1 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% potassium carbonate solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 120°C and 0.1 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 120°C and 0.1 MPa to recover the solvent, and the recovered solvent was combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0023] Example 6 9.5 g of propylene glycol monomethyl ether, 0.5 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 20% sodium carbonate solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.01 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.001 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0024] Example 7 5g of propylene glycol monomethyl ether, 5g of deionized water, 102mg of 98% concentrated sulfuric acid, and 1g of straw powder were added to a 50mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100kPa for 3h. After the reaction, the pH was adjusted to 6.5 with solid calcium hydroxide powder, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 90°C and 0.005MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.001MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0025] Example 8 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 255 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 80°C and 40 kPa for 5 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.01 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.001 MPa to recover the solvent, and the recovered solvent was combined and weighed. To the filtrate residue after solvent recovery, 10 times the mass of water was added, stirred, and then solid-liquid separation was performed. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0026] Example 9 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 255 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 90°C and 60 kPa for 5 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 85°C and 0.005 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 85°C and 0.005 MPa to recover the solvent, and the recovered solvent was combined and weighed. To the filtrate residue after solvent recovery, 10 times the mass of water was added, stirred, and then solid-liquid separation was performed. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0027] Example 10 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 10.2 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 160°C and 800 kPa for 20 min. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 120°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 100°C and 0.002 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0028] Example 11 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 255 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 130°C and 300 kPa for 1 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 110°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.007 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0029] Example 12 8 g of propylene glycol monomethyl ether, 1.89 g of deionized water, 200.6 mg of 37% concentrated hydrochloric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 110°C and 0.008 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 90°C and 0.002 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0030] Example 13 8 g of propylene glycol monomethyl ether, 1.96 g of deionized water, 78.82 mg of 85% phosphoric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.01 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.001 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0031] Example 14 8 g of propylene glycol monomethyl ether, 2 g of deionized water, 126.05 mg of 85% phosphoric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 80°C and 0.001 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 120°C and 0.05 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0032] Example 15 8 g of ethylene glycol monomethyl ether, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 2.5 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 85°C and 0.005 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 85°C and 0.005 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0033] Example 16 8 g of ethylene glycol monomethyl ether, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 90°C and 0.002 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 90°C and 0.002 MPa to recover the solvent, and the recovered solvent was combined and weighed. To the filtrate residue after solvent recovery, 10 times the mass of water was added, stirred, and then solid-liquid separation was performed. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0034] Example 17 9 g of ethylene glycol monoethyl ether, 1 g of deionized water, 25.5 mg of 98% concentrated sulfuric acid, and 1 g of eucalyptus powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 5 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.002 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 100°C and 0.002 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0035] Example 18 9 g of propylene glycol monoethyl ether, 1 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of eucalyptus powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid component and a filtrate. The cellulose solid component was distilled at 120°C and 0.0.01 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose component. The filtrate was distilled at 120°C and 0.0.01 MPa to recover the solvent, and the recovered solvent was combined and weighed. To the filtrate residue after solvent recovery, 10 times the mass of water was added, stirred, and then solid-liquid separation was performed. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin component. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0036] Example 19 4 g of propylene glycol monomethyl ether, 4 g of ethylene glycol monomethyl ether, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 110°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 110°C and 0.05 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0037] Comparative Example 1 6.31 g of ethanol, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 405 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.05 MPa to recover the solvent, and the recovered solvent was combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0038] As shown in Table 1, compared with Example 1, it can be found that at the same temperature, the operating pressure reaches 405 kPa. Under this condition, the extraction rate of lignin is only 7.69%.

[0039] Comparative Example 2 6.31 g of ethanol, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 180°C and 1.7 MPa for 2 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.05 MPa to recover the solvent, and the recovered solvent was combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent recovery, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0040] As shown in Table 1, compared with Example 1, it can be found that when the reaction is carried out at a high temperature and the operating pressure reaches 1.7 MPa, under this condition, the yield of hemicellulose sugar is only 4.59%.

[0041] Comparative Example 3 8.90 g of ethylene glycol, 2 g of deionized water, 102 mg of 98% concentrated sulfuric acid, and 1 g of straw were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 20 kPa for 3 h. After the reaction, the pH was adjusted to 6-7 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid component and a filtrate. The cellulose solid component was washed three times with 15 mL of water, and the washings were collected. The washed cellulose solid component was dried at 100°C and 0.05 MPa to constant weight. 100 mL of water was added to the filtrate, stirred, and then solid-liquid separation was performed. The resulting solid was dried to obtain lignin, which was then weighed. The filtrate was combined with the cellulose solid component washings. 98% concentrated sulfuric acid was added to the combined solution to adjust the pH to 0.7, and hydrolysis was performed at 100°C for 1 h to obtain a crude sugar solution containing hemicellulose sugars. The masses of the separated components are shown in Table 1.

[0042] As shown in Table 1, compared with Example 1, it can be found that since the boiling point of ethylene glycol is as high as 197°C, it is difficult to directly dry or distill the cellulose solid component and recover the ethylene glycol in the filtrate. Therefore, a large amount of water is required to wash the cellulose solid and precipitate the lignin.

[0043] Comparative Example 4 8 g of dioxane, 2 g of deionized water, 10.2 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 200 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.05 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0044] As shown in Table 1, compared with Example 1, it can be found that since dioxane does not contain hydroxyl groups, it cannot inhibit the degradation and condensation of lignin and sugars, and a large amount of hemicellulose sugars are degraded, with a yield of only 9.32%.

[0045] Comparative Example 5 8 g of n-butanol, 2 g of deionized water, 10.2 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.05 MPa to recover the solvent, and the recovered solvent was combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0046] As shown in Table 1, compared with Example 1, it can be found that n-butanol with a boiling point of 118° C. does not contain ether bonds, and the lignin dissolution effect at this temperature is poor, and the separation effect under the same conditions is poor.

[0047] Comparative Example 6 8 g of n-butyl acetate, 2 g of deionized water, 10.2 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.05 MPa to recover the solvent, and the recovered solvent was combined and weighed. To the filtrate residue after solvent recovery, 10 times the mass of water was added, stirred, and then solid-liquid separation was performed. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0048] As shown in Table 1, it can be found from Comparative Example 1 that since n-butyl acetate with a boiling point of 126° C. is poorly soluble in water, the separation effect is poor.

[0049] Comparative Example 7 8 g of methyl isobutyl ketone, 2 g of deionized water, 10.2 mg of 98% concentrated sulfuric acid, and 1 g of straw powder were added to a 50 mL stainless steel reactor. The reactor was sealed and heated, with stirring at 120°C and 100 kPa for 3 h. After the reaction, the pH was adjusted to 6.5 with 50% sodium hydroxide solution, and the reaction mixture was filtered to obtain a cellulose-containing solid fraction and a filtrate. The cellulose solid fraction was distilled at 100°C and 0.05 MPa to recover the solvent, dried to a constant weight, and weighed to obtain the mass of the cellulose fraction. The filtrate was distilled at 80°C and 0.05 MPa to recover the solvent, and the recovered solvents were combined and weighed. Ten times the mass of water was added to the filtrate residue after solvent distillation, stirred, and then subjected to solid-liquid separation. The resulting solid was dried to obtain lignin, which was weighed to obtain the mass of the lignin fraction. The resulting filtrate contained hemicellulose sugars and their derivatives. The filtrate was then hydrolyzed at 100°C for 1 hour to obtain an extract containing hemicellulose sugars. The mass of the hemicellulose sugars was determined by ion chromatography. The masses of the separated components are shown in Table 1.

[0050] As shown in Table 1, it can be found from Comparative Example 1 that since methyl isobutyl ketone with a boiling point of 116° C. is only slightly soluble in water, the separation effect is poor.

[0051] Table 1: Reaction conditions and results A comparison of Examples 1 and 2 shows that, given the same amount of vicinal glycol monoether compound, a greater amount of acid added facilitates effective separation of the three components. A comparison of Examples 1, 3, and 4 shows that vicinal glycol monoether compounds are suitable for a variety of biomass types. A comparison of Examples 4, 5, 6, and 7 shows that increasing the proportion of vicinal glycol monoether compounds leads to a gradual decline in separation efficiency and an increase in fiber component retention. This is due to ineffective removal of lignin and hemicellulose. The best results are achieved when the organic compound:water ratio is between 8:2 and 9.5:0.5. A comparison of Examples 8, 9, 10, and 11 shows that increasing the temperature or extending the reaction time facilitates effective separation of the three components. Example 10 demonstrates that using higher temperatures can easily lead to degradation of hemicellulose sugars. The best separation results were achieved in Example 12, which achieved a reaction temperature of 120°C and a reaction time of 3 hours. From the comparison of Example 1 with Example 12, Example 13 and Example 14, it can be seen that different medium-strong acids can catalyze the separation of the three components, but phosphoric acid has a slightly worse separation effect due to its weaker acidity than sulfuric acid and hydrochloric acid. It can be seen from the comparison of Example 1 with Example 15 that after increasing the amount of straw added, the three components can still be separated well. In Example 19, ethylene glycol monomethyl ether and propylene glycol monomethyl ether also demonstrate a good separation effect on the three components of biomass.

[0052] It should be noted that when the claims of the present invention involve numerical ranges, it should be understood that the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. In order to avoid redundancy, the present invention describes preferred embodiments.

[0053] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0054] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.

Claims

1. A method for separating woody biomass components using medium-boiling point alcohol ether compounds, characterized in that: The following steps are involved: S1. Mixing plant wood, a vicinal glycol monoether compound, water, and an acid, reacting the mixture in a closed reactor for 0.5 to 5 hours, adjusting the pH to 6 to 7, and separating to obtain a cellulose solid component and a filtrate A; S2. Drying the cellulose solid component to a constant weight to obtain a cellulose component, condensing and recovering the solution containing the vicinal glycol monoether compound during the drying process, distilling the filtrate A to recover the solution containing the vicinal glycol monoether compound to obtain a residue, adding water to the residue, stirring, and performing solid-liquid separation to obtain a lignin solid component and a filtrate B; S3. Dry the lignin solid component to a constant weight to obtain a lignin component, and adjust the pH of the filtrate B to 0.6-0.8 and hydrolyze for 0.5-1.5 h to obtain a hemicellulose sugar component.

2. The method for separating woody biomass components using a medium-boiling alcohol ether compound according to claim 1, wherein: The vicinal glycol monoether compound is selected from any one of ethylene glycol monomethyl ether, 1,2-propylene glycol-1-monomethyl ether, ethylene glycol monoethyl ether, and 1,2-propylene glycol-1-monoethyl ether.

3. The method for separating woody biomass components using a medium-boiling point alcohol ether compound according to claim 1, wherein: The mass ratio of the plant wood, vicinal glycol monoether compound, water and acid in S1 is 0.5~2.5:5~15:0.5~4.5:0.01~0.

3.

4. The method for separating woody biomass components using a medium-boiling alcohol ether compound according to claim 1, wherein: The reaction conditions in the closed reactor are 80-140° C. and 90-110 kPa.

5. The method for separating woody biomass components using medium-boiling point alcohol ether compounds according to claim 1, characterized in that: The drying conditions are 80-120° C. and 0.001-0.1 MPa.

6. The method for separating woody biomass components using medium-boiling point alcohol ether compounds according to claim 1, characterized in that: The mass ratio of the residue to water in S2 is 0.5-1.5:9-11.

7. The method for separating woody biomass components using medium-boiling point alcohol ether compounds according to claim 1, characterized in that: The distillation conditions are 80-120° C. and 0.001-0.1 MPa.

8. The method for separating woody biomass components using medium-boiling point alcohol ether compounds according to claim 1, characterized in that: The acid is selected from any one of 98% by mass sulfuric acid, 37% by mass hydrochloric acid, and 85% by mass phosphoric acid.